Determination of 11 Cannabinoids in Biomass and Extracts of Different Varieties of Cannabis Using High-Performance Liquid Chromatography. (27th November 2019) - Gul, Waseem; Gul, Shahbaz W; Radwan, Mohamed M; Wanas, Amira S; Mehmedic, Zlatko; Khan, Ikhlas I; Sharaf, Maged H M; ElSohly, Mahmoud A
Abstract: An HPLC single-laboratory validation was performed for the detection and quantification of the 11 major cannabinoids in most cannabis varieties, namely, cannabidiolic acid (CBDA), cannabigerolic acid (CBGA), cannabigerol (CBG), cannabidiol (CBD), tetrahydrocannabivarin (THCV), cannabinol (CBN), Δ 9 - trans -tetrahydrocannabinol (Δ 9 -THC), Δ 8 - trans -tetrahydrocannabinol (Δ 8 -THC), cannabicyclol (CBL), cannabichromene (CBC), and Δ 9 -tetrahydrocannabinolic acid-A (THCAA). The analysis was carried out on the biomass and extracts of these varieties. Methanol–chloroform (9:1, v/v) was used for extraction, 4-androstene-3, 17-dione was used as the internal standard, and separation was achieved in 22.2 min on a C18 column using a two- step gradient elution. The method was validated for the 11 cannabinoids. The concentration-response relationship of the method indicated a linear relationship between the concentration and peak area with r 2 values of >0.99 for all 11 cannabinoids. Method accuracy was determined through a spike study, and recovery ranged from 89.7 to 105.5% with an RSD of 0.19 to 6.32% for CBDA, CBD, THCV, CBN, Δ 9 -THC, CBL, CBC, and THCAA; recovery was 84.7, 84.2, and 67.7% for the minor constituents, CBGA, CBG, and Δ 8 -THC, respectively, with an RSD of 2.58 to 4.96%. The validated method is simple, sensitive, and reproducible and is therefore suitable for the detection and quantification of these cannabinoids in different types of cannabis plant materials.